2021
DOI: 10.1371/journal.pone.0257124
|View full text |Cite
|
Sign up to set email alerts
|

AIR-BT, a new badminton-specific incremental easy-to-use test

Abstract: Background Badminton is a highly demanding sport characterized by intermittent efforts with energy being provided by both the aerobic and anaerobic systems. To date, no incremental badminton field test has been developed that can be easily used by badminton coaches that requires accessible material for anyone. Objectives The purpose of this study was to develop a practical and reliable easy-to use intermittent endurance badminton test for estimating maximal oxygen uptake (VO2max). Methods Thirty six Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…However, laboratory testing is ineffective at replicating the sport-specific physiological and biomechanical particularities of badminton, such as the multidirectional movement patterns and muscular contractions that are undertaken on the court [ 28 ]. Therefore, the applicability of these methodologies to an intermittent sport with frequent changes of direction and fluctuations in movement velocity remains questionable [ 29 ]. Similarly, researchers attempting to conduct physiological profiling of racket sports often estimate pulmonary oxygen uptake indirectly under the assumption of a linear relationship with heart rate [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, laboratory testing is ineffective at replicating the sport-specific physiological and biomechanical particularities of badminton, such as the multidirectional movement patterns and muscular contractions that are undertaken on the court [ 28 ]. Therefore, the applicability of these methodologies to an intermittent sport with frequent changes of direction and fluctuations in movement velocity remains questionable [ 29 ]. Similarly, researchers attempting to conduct physiological profiling of racket sports often estimate pulmonary oxygen uptake indirectly under the assumption of a linear relationship with heart rate [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results would be helpful in monitoring the condition of badminton players, especially elite players, because they spend a lot of time on skill/strength training, traveling, and participating in international tournament activities. Therefore, it would be difficult to find time for all‐out tests developed in previous studies (Abián‐Vicén et al., 2021 ; Chin et al., 1995 ; Madsen et al., 2016 ). This study showed that BLa increased to 3.0–4.6 mM in ranked players at stage 2 (similar tempo with Singles match) of the badminton‐specific endurance test, which is similar to BLa in badminton matches (Faude et al., 2007 ; Fernandez‐Fernandez et al., 2013 ; Green et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies adopted continuous exercises (e.g., 3 min of badminton‐specific exercise with a rest of 45 s and a work:rest ratio of 4:1 or 30–12 s of badminton‐specific exercise with a rest of 10 s and a work:rest ratio of approximately 3:1–1:1) with all‐out efforts in their on‐court endurance tests (Abián‐Vicén et al., 2021 ; Chin et al., 1995 ; Madsen et al., 2016 ). However, badminton games have been characterized as submaximal load, such as 54%–80% of peak oxygen uptake and 1.9–4.3 mM for BLa (Faude et al., 2007 ; Fernandez‐Fernandez et al., 2013 ; Green et al., 2023 ), and intermittent exercises (Phomsoupha & Laffaye, 2015 ), such as 4.8–10.4 s of rally duration with rest of 8.1–26.7 s (i.e., work: rest ratio is approximately 1:2; Abdullahi & Coetzee, 2017 ; Gawin et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bulutangkis adalah salah satu olahraga yang paling umum dilakukan di dunia dan semakin populer di seluruh dunia (Abia´n-Vice´n et al, 2021). Badminton adalah olahraga raket yang sangat populer dan diterima secara universal yang dimainkan di seluruh dunia.…”
Section: Pendahuluanunclassified